2D axial-azimuthal particle-in-cell benchmark for low-temperature partially magnetized plasmas. (17th October 2019) - Charoy, T; Boeuf, J P; Bourdon, A; Carlsson, J A; Chabert, P; Cuenot, B; Eremin, D; Garrigues, L; Hara, K; Kaganovich, I D; Powis, A T; Smolyakov, A; et al.
Abstract: The increasing need to demonstrate the correctness of computer simulations has highlighted the importance of benchmarks. We define in this paper a representative simulation case to study low-temperature partially-magnetized plasmas. Seven independently developed particle-in-cell codes have simulated this benchmark case, with the same specified conditions. The characteristics of the codes used, such as implementation details or computing times and resources, are given. First, we compare at steady-state the time-averaged axial profiles of three main discharge parameters (axial electric field, ion density and electron temperature). We show that the results obtained exhibit a very good agreement within 5% between all the codes. As E × B discharges are known to cause instabilities propagating in the direction of electron drift, an analysis of these instabilities is then performed and a similar behaviour is retrieved between all the codes. A particular attention has been paid to the numerical convergence by varying the number of macroparticles per cell and we show that the chosen benchmark case displays a good convergence. Detailed outputs are given in the supplementary data, to be used by other similar codes in the perspective of code verification.